Effective strategic management model of university student’s association in Nanchang city - Kuai, Lu; Siththada, Thada (Edelweiss Applied Science and Technology, 2024)
This study investigates the strategic management of university student associations (USAs) in Nanchang City, focusing on seven key factors: government support, communication and feedback, resource utilization and allocation, event organization and scheduling, association management and leadership, management transparency and accountability mechanisms, and teamwork and atmosphere. Using a mixed-method approach, data were collected from 540 respondents across 36 universities through structured surveys and interviews. Descriptive statistics and exploratory factor analysis (EFA) revealed that leadership effectiveness, transparent governance, resource optimization, and collaborative teamwork significantly enhance organizational performance and member engagement. The study proposes a comprehensive management model tailored to the context of Nanchang City, offering actionable strategies to address identified challenges. These findings contribute to the understanding of effective governance in higher education, providing practical insights for improving the operational efficiency and strategic alignment of student associations.